Edukasi Latihan Pelvic Tilting untuk Kasus Ischialgia pada kondisi Lansia di wilayah Puskesmas Mojolaban - Ivana Hanun Nisa; Farid Rahman; Eni Susilowati (Asosiasi Riset Ilmu Matematika dan Sains Indonesia, 2024)
Mojolaban is a sub-district in Sukoharjo Regency, Central Java which has 15 villages. This sub-district has a Mojolaban main health center and a Jatimalang sub-district health center. Mojolaban sub-district has many elderly people aged 60-64 years, 42,481 people and most of them work as ethanol, roof tile and gamelan craftsmen. Ischialgia has risk factors such as age, unergonomic working positions, the habit of lifting too heavy weights, and injury. These risk factors are related to the majority of people's jobs in the Mojolaban District area. Ischialgia is a problem that often arises in the elderly and people in Mojolaban District do not yet know how to treat Ischialgia properly. This outreach method uses the lecture method and uses leaflets as an outreach medium. The aim of this outreach is to prevent, promote health related to Ischialgia, targeting participants at the Elderly Posyandu located in Palur Mojolaban Village. The measurements used in this activity were pre-test and post-test questionnaires to measure the elderly's understanding of Ischialgia. The results showed a significant increase in understanding regarding Ischialgia material with an average pre-test score of 3.5 and an average post-test score of 6.1.